SECRETARY’S REPORT FROM CASTERBRIDGE - NIXON, MIKE (Thomas Hardy journal, 2017)
After a couple of emails confirming the colours of the merchandise, and interestingly, some intensive research regarding shipping carriers, the large package was dispatched to Mexico - and arrived safely, much to the joy of the recipient and us! Another outlet for our merchandise Whilst on the subject of our excellent merchandise, we are always seeking ways of bringing it to the attention of the general public,(as well as to remind members of what's available with Christmas coming) and we have established an excellent new outlet in the lovely village of Evershot (Hardy's Evershead), at their village shop. Today you can walk through a dense forest of darkness when you come to the area that has been cleared, and in the right season, is a carpet of bluebells.